Towards academic computer emergency response teams in African developing countries - Mutembei, Leonard; Ishengoma, Fredrick (Association for Scientific Computing Electrical and Engineering, 2021)
The increasing number of cyberattacks on African universities demonstrates the critical need for a more profound shift in perspective from a simple IT problem to the implementation of more resilient security measures and policies, and thus, Computer Emergency Response Teams (CERTs). Fortunately, even though there are numerous CERTs worldwide, there are relatively few studies in the literature that address academic-CERT in the African context. This article summarizes the CERT landscape in African countries and proposes a framework for academic-CERT. The proposed framework aims to fortify African academic institutions' resilient security measures. The paper will serve as a foundation for developing academic CERTs in African countries, which will eventually result in the implementation of national CERTs and the protection of online users.